(untitled) (Medico Legal Update, 2021)
The study aimed to find the relation between Covid-19 infection and reduction in vitamin-D levels and with development of severe infection The study was conducted in Kirkuk city during July 2020, included 120 COVID-19 patients who diagnosed by collecting of naso/oropharyngeal swabs and the virus RNA was qualitatively detected by real-Time PCR in Public Health Laboratory according manufacture instruction and WHO protocol. The study also included 30 healthy persons as control group. The study included the collection of blood samples for determination of vitamin-D level (I-chroma, Korea) by direct immunofluorescence technique and according to manufacture instruction. The study also included collection of associated information like age, sex, residence, BMI and by contacting with all patients daily until the 10th day of infection to know their status after treatment. The study showed that, majority of patients were aged from 22 to 41 years of old (P. value <0.001). The study showed that 62.5% of COVID-19 patients were males compared with 37.5% females (P<0.05). The study showed that were asymptomatic, 44.17% of cases of COVID-19 patients were with mild infection and 10% were with severe infection (P<0.001). The study showed a significant relation between Covid-19 infection status with age as the highest mean of age of Covid-19 infected patients was recorded in those who with severe infection. The study showed that the lowest mean of serum Vitamin was found in COVID-19 patients comparing with healthy control (12.8±3.6 v.s. 29.3±3.1 ng/ml) (P: <0.001). The study also demonstrated that the level of vit. D was significantly reduced in severe infected COVID-19 patients followed by patients with moderate infection and the highest mean was in patients with asymptomatic infection (P<0.001).